The relationship between emotional intelligence, spiritual and students stress facing online learning during the Covid pandemic - Mamat, Suzyliana; Wan Othman, Wan Norhayati; Alias, Atini; Yahya, Siti Aishah; Abdullah, Norhasima; Omar Mokhtar, Muhammad Yasin (Human Resource Management Academic Research Society, 2022)
The Covid pandemic has altered the daily routines of humans. Students have been compelled to study from home, utilising an online learning platform. Students were stressed and dissatisfied as a result of the abrupt change in their learning environment. The purpose of this study is to examine the relationship between emotional intelligence, spirituality, and the stress that students experience when participating in online learning during the global pandemic. Relevant articles were chosen from databases such as Scopus, PudMed, ScienceDirect, and Google Scholar. It was decided to look at research published between 2012 and 2021 in order to examine the emotional intelligence, spirituality, and student stress associated with online learning. The finding shows that emotional intelligence and spiritual is significant correlated with students stress. Students' stress levels were predicted by their online learning experiences. A discussion is also held about the implications of the article, specifically about how a counsellor can improve their counselling services so that they can better assist students in dealing with their study stress while using an online learning method.